FPO Emerging as the New MSME or Village Industry. Issue 1 (March 2019) - Seshagiri Rao, P. V. S.
The fledgling farmer producer organisations (FPO) have a statutory status but need better appreciation. They have a crucial role in doubling the farmer's income. Seventy-five National Bank for Agriculture and Rural Development (NABARD) funded FPOs in Telangana (out of 129 FPOs among the thousands of enterprises in the state formed/funded up to the year 2018) were studied—starting with a numerical perspective before moving onto an entrepreneurial study in this desk-based analysis. The coverage has been found to be skewed in 59 (out of 584 ) mandals (blocks) in 23 (out of 31) districts in Telangana. The top as well as poorly performing three districts each have been identified for further action besides proposing the use of a metric of FPO density/1000 cultivators. It is also to be noted that eight districts (accounting for about a third of the cultivator population) have been left uncovered by the FPO activity (especially Hyderabad district which can be a crucible for unique and novel enterprises). The interactions of FPO-promoters and FPO-age have been studied. Their entrepreneurial activities have been examined and it was found to be diverse with little value addition in these and little service activity taken up. It seeks to further the argument that FPOs can be equated with micro, small and medium enterprises (MSMEs)/village industries so that benefits to industries also flow here. The author agrees with the results of the Global Entrepreneurship Monitor study regarding entrepreneurial behaviour. It is proposed to examine in a serial manner the growth, membership, financial stakes, etc. in the future studies for their greater understanding.